Pengaruh Kualitas Layanan Elektronik terhadap Kepuasan Masyarakat yang Menggunakan Aplikasi Napigo 2.2 di Rutan Kelas I Labuhan Deli - Esternia Naibaho; Naniek Pangestuti (AS-SABIQUN, 2023)
This study aims to determine the effect of the quality of electronic services on the satisfaction of the people who use the NapiGO 2.2 application at the Rutan Class I in Labuhan Deli. The method used in this research is quantitative which uses two types of data, namely primary data and secondary data. Primary data is obtained from the distribution of questionnaires and secondary data, namely journals, books and previous studies which are linear with research. The object used in this study is the community or family of prisoners who use the NapiGo 2.2 application at the Rutan Class I in Labuhan Deli. This study was conducted on 96 respondents with a total of 35 questionnaires used which were divided into 21 statements for the X variable and 14 statements for the Y variable. This study used data quality test methods, namely validity test, reliability test, normality test, simple linear regression test. , determination test, and significance test using SPSS 22 software. Based on the analysis carried out, the results showed that the quality of electronic services had an effect on the satisfaction of the people who used the NapiGo 2.2 application at the Rutan Class I in Labuhan Deli, as evidenced by the results of the t test calculation ( significance) it was found that the value of t arithmetic > t table obtained was 8.031 > 1.985 which means that the value of Ho was rejected and Ha was accepted. Determination test obtained R Square of 40.7% or 0.407 which shows the large influence of the variable quality of electronic service as an independent variable on the variable of community satisfaction as the dependent variable while the remaining 59.3% is influenced by other factors not in this study.